Basis for the Mutational Acquisition of the Ability of Aerobacter aerogenes to Grow on l-Mannose - Mayo, Joseph W. (1969)
Growth of Aerobacter aerogenes PRL-R3 on the unnatural hexose l-mannose as a sole carbon source is dependent upon the selection of a mutant. Growth of the mutant on l-mannose did not require the synthesis of novel enzymes for the degradation of l-mannose, since enzymes of the l-rhamnose degradative pathway could serve this function. However, unlike most other apparent gain mutations that have been described, the mutant was not constitutive for the degradative enzymes; isomerase, kinase, and aldolase activities functional in the degradation of both l-mannose and l-rhamnose were induced by either of these hexoses in the wild type as well as in the mutant. The fact that the wild type could metabolize l-mannose also ruled out the possibility that the cells were not permeable to l-mannose. Growth of the wild type on nutrient broth was severely inhibited by l-mannose coincident with the onset of l-mannose metabolism. A similar inhibition of growth of the mutant was overcome in about 2 hr. Both strains utilized l-rhamnose and l-mannose sequentially in a mineral medium containing both of these hexoses; at the onset of l-mannose metabolism, growth of the wild type, but not of the mutant, was inhibited. Thus, wild-type A. aerogenes cannot grow on l-mannose because of the toxicity of l-mannose or its metabolites. A mutation which overcomes the toxicity enables the organism to utilize l-mannose as a sole source of carbon and energy for growth.